(untitled) (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Djeddar H, Boudjelida H, Arroussi DER. 2021. New alternative for culicidian fauna control using Borago officinalis and Drimia maritima plant extracts. Biodiversitas 22: 5688-5694. Focus on the development of insecticides based on botanical extracts may represent an alternative environmentally interesting tool to chemical control. The current study aimed to investigate the effects of both extracts of Drimia maritima (Asparagales: Asparagaceae) and Borago officinalis (Lamiales: Boraginaceae) on larvae sensibility, physiological and biochemical parameters of Culex pipiens (Diptera: Culicidae). The larvicidal bioassay exhibits a significant dose-response relationship against the fourth instar larvae of Cx. pipiens. Moreover, biochemical analyses revealed a decrease in proteins levels, carbohydrates and lipids in the whole larvae body treated with the lethal concentrations (LC50, LC90) of D. maritima extract as compared to the control series. Whereas, using B. officinalis herbal plants, the result showed a decrease in lipid and carbohydrate contents and an increase in protein. The ability of D. maritima and B. officinalis extracts to inhibit acetylcholinesterase (AChE) activity in a whole body of the treated larvae of Cx. pipiens is examined. The estimated specific activity of glutathione S-transferase (GST) at different times was significantly increased under the effects of both plants. The present study demonstrates that the aqueous extracts of D. maritima and B.officinalis present insecticidal properties with neurotoxic effects against larval stages of the domestic mosquito Cx. pipiens. In this context, the use of chemical insecticides for mosquito control is no longer recommended and the alternatives of eco-friendly products are encouraged.